2019
DOI: 10.3390/molecules24132347
|View full text |Cite
|
Sign up to set email alerts
|

Populations and Dynamics of Guanine Radicals in DNA strands—Direct versus Indirect Generation

Abstract: Guanine radicals, known to be involved in the damage of the genetic code and aging, are studied by nanosecond transient absorption spectroscopy. They are generated in single, double and four-stranded structures (G-quadruplexes) by one and two-photon ionization at 266 nm, corresponding to a photon energy lower than the ionization potential of nucleobases. The quantum yield of the one-photon process determined for telomeric G-quadruplexes (TEL25/Na+) is (5.2 ± 0.3) × 10−3, significantly higher than that found fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 78 publications
6
55
0
Order By: Relevance
“…28 Coming to radicals, their spectra ( Figure 3) are determined after the decay of e hyd -. As in the case of previously studied G-quadruplexes, [4][5][6] the spectrum at 3 µs exhibits a broad band in the visible, explained by the coexistence of (G) + and (G-H2)  . When the transient absorbance A is divided by the [e hyd -] 0 determined for the same excitation intensity, the radical spectrum can be quantitatively described by a linear combination of the (G) + and (G-H2)  spectra in a ratio 0.4/0.6 (Figure 3a), considering the corresponding spectra reported for either monomeric guanosines [29][30] or (TG4T) 4 /Na + .…”
supporting
confidence: 73%
See 1 more Smart Citation
“…28 Coming to radicals, their spectra ( Figure 3) are determined after the decay of e hyd -. As in the case of previously studied G-quadruplexes, [4][5][6] the spectrum at 3 µs exhibits a broad band in the visible, explained by the coexistence of (G) + and (G-H2)  . When the transient absorbance A is divided by the [e hyd -] 0 determined for the same excitation intensity, the radical spectrum can be quantitatively described by a linear combination of the (G) + and (G-H2)  spectra in a ratio 0.4/0.6 (Figure 3a), considering the corresponding spectra reported for either monomeric guanosines [29][30] or (TG4T) 4 /Na + .…”
supporting
confidence: 73%
“…They were excited by 5 ns laser pulses at 266 nm ( Figure SI-1), with incident intensity lower than 2x10 6 Wcm -2 , thus avoiding two-photon ionization of the solvent. Two different scenarios were invoked to explain G-quadruplex ionization by low-energy photons: [5][6] (A) the specific arrangement of guanines lowers their VIP, or (B) electron detachment occurs after excited state relaxation towards charge transfer (CT) states.…”
mentioning
confidence: 99%
“…Accordingly, the transient absorption signals at 512 nm shown in Figure 5 , where the intensity at 3 µs is normalized to 1, represents the survival probability P t of the total radical population at time t, i.e., the fraction of the initial radical concentration at time t: P t = [R] t /[R] 0 . For a quantitative description, the experimental traces recorded on the microsecond and millisecond time-scale were fitted with bi-exponential functions, although such fits have no physical meaning [ 10 ]. Thus, we found that the radical decay spans more than four orders of magnitude; at 50 µs, 80% of the radical population is present, while at 10 ms, this percentage dwindles down to 20%.…”
Section: Resultsmentioning
confidence: 99%
“…We showed that two different processes take place. First, deprotonation of radical cations occurs in the position 2, giving rise to (G-H2) • radicals instead of the (G-H1) • radicals (Figure 1a), which are observed for the dGMP mononucleotide [13] and various duplexes [10,14,15]. Such a different deprotonation route, which was initially detected by photosensitized oxidation of G-quadruplexes [16], is due to the fact The above-mentioned studies were performed by transient absorption spectroscopy using not only low-energy (266 nm) but also low-intensity excitation (5 ns laser pulses, incident intensity lower than 2 × 10 6 Wcm −2 ).…”
Section: Tel21/na + [8] Tel25/na + [10] (Tg4t)4/na + [9] (Tg4t)4/k + mentioning
confidence: 99%
See 1 more Smart Citation